2021
DOI: 10.1161/circimaging.121.012459
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric Early Detection and Prediction of Cardiotoxicity Using Myocardial Strain, T1 and T2 Mapping, and Biochemical Markers: A Longitudinal Cardiac Resonance Imaging Study During 2 Years of Follow-Up

Abstract: Background: Our goal was to evaluate the ability of cardiovascular magnetic resonance for detecting and predicting cardiac dysfunction in patients receiving cancer therapy. Left ventricular ejection fraction, global and regional strain utilizing fast-strain-encoded, T1 and T2 mapping, and cardiac biomarkers (troponin and BNP [brain natriuretic peptide]) were analyzed. Methods: Sixty-one patients (47 with breast cancer, 11 with non-Hodgkin lymphoma, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 38 publications
2
23
0
Order By: Relevance
“…Finally, the use of additional imaging techniques such as cardiac magnetic resonance, including regional strain or T1 and T2 mapping could add more accurate and sensitive information for the detection of cardiotoxiciy. 24 Nevertheless, these novel techniques are not widely available in many centres, they require higher expertise and analysis might be challenging.…”
Section: Limitationsmentioning
confidence: 99%
“…Finally, the use of additional imaging techniques such as cardiac magnetic resonance, including regional strain or T1 and T2 mapping could add more accurate and sensitive information for the detection of cardiotoxiciy. 24 Nevertheless, these novel techniques are not widely available in many centres, they require higher expertise and analysis might be challenging.…”
Section: Limitationsmentioning
confidence: 99%
“…The relative reduction of LV-GRS observed in the CTRCD group was than that in the non-CTRCD group and had a predictive value in identifying the CTRCD population at the early stage of ICI therapy (3 months). The value of LV strain in predicting cardiotoxicity in patients receiving cancer therapy has been confirmed (28). It is very important to explore the feasibility of CMR indexes in predicting the development of cardiotoxicity before starting or during the cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely demonstrated that NT-proBNP and hs-TnT levels increase during cancer therapy, although their utility for cardiotoxicity prediction has been questioned [ 6 , 13 , 17 , 18 , 19 , 20 , 21 , 22 ]. In this study, we have reported ACC-induced increments in these biomarkers associated with an early reduction of LV contractility, as assessed by GLS at 3 months after ACC completion, with NT-proBNP also showing an association with a higher risk of cardiotoxicity 12 months after ACC completion.…”
Section: Discussionmentioning
confidence: 99%